(untitled) (Revista Contexto & Saúde, 2026)
Objective: To evaluate the working conditions and risk factors for illness among nursing professionals. Method: A cross-sectional and quantitative study was conducted in a healthcare institution in Southwest Minas Gerais, with 90 nursing professionals. Data were collected using two instruments: a semi-structured questionnaire for sociodemographic, epidemiological, occupational, and working conditions information; and the Inventory of Work and Illness Risks to assess illness indicators among professionals. Results: The variables age, alcohol consumption, length of professional experience, workload, job valuation, and work accidents were found to be associated with the work organization factor (P < 0.05) and also with the physical cost of work for hospital nursing professionals (P < 0.05). The other factors, i.e., working conditions and physical damage, did not show a significant association with the independent variables. Conclusion: Working conditions are directly or indirectly related to illness among nursing workers. Based on this, it is worth considering actions that mitigate these impacts, in order to improve the physical and mental health of professionals.